Brewer–Dobson Circulation: Recent-Past and Near-Future Trends Simulated by Chemistry-Climate Models. (11th June 2017) - Hu, Dingzhu; Guo, Yipeng; Wang, Feiyang; Xu, Qi; Li, Yuanpu; Sang, Wenjun; Wang, Xudong; Liu, Meichen
Abstract : Based on data from 16 chemistry-climate models (CCMs) and separate experimental results using a state-of-the-art CCM, the trends in the Brewer–Dobson circulation (BDC) during the second half of the 20th century (1960–2000) and the first half of the 21st century (2001–2050) are examined. From the ensemble mean of the CCMs, the BDC exhibits strengthening trends in both the 20th and 21st centuries; however, the acceleration rates of tropical upwelling and southern downwelling during 2001–2050 are smaller than those during 1960–2000, while the acceleration rate of the northern downward branch of the BDC during 2001–2050 is slightly larger than that during 1960–2000. The differences in the extratropical downwelling trends between the two periods are closely related to changes in planetary-wave propagation into the stratosphere caused by the combined effects of increases in the concentrations of greenhouse gases (GHGs) and changes in stratospheric ozone. Model simulations demonstrate that the response of southern downwelling to stratospheric ozone depletion is larger than that to the increase in GHGs, but that the latter plays a more important role in the strengthening of northern downwelling. This result suggests that, under the expected future climate, northern downwelling will play a more important role in balancing tropical upwelling.